2010
DOI: 10.14295/bds.2008.v11i2.457
|View full text |Cite
|
Sign up to set email alerts
|

Concentração fungicida mínima das soluções de clorexidina e hipoclorito de sódio sobr Candida Albicans

Abstract: A clorexidina e o hipoclorito de sódio são agentes irrigantes comumente utilizados na Endodontia em diferentes concentrações.A concentração fungicida mínima destas soluções sobre leveduras do gênero Candida, que são microrganismos freqüentemente associados a infecções endodônticas secundárias e/ou persistentes, é raramente discutida na literatura.Desta forma, a proposta deste estudo foi avaliar a concentração fungicida mínima das soluções irrigadoras clorexidina e hipoclorito de sódio sobre cepas de C. albican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
2
7
0
4
Order By: Relevance
“…The present study showed similar results to those obtained by Menezes et al. , [7] with lower MIC and MFC values for chlorhexidine than for sodium hypochlorite. Xavier et al.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present study showed similar results to those obtained by Menezes et al. , [7] with lower MIC and MFC values for chlorhexidine than for sodium hypochlorite. Xavier et al.…”
Section: Discussionsupporting
confidence: 92%
“…A standard protocol has not been established as yet. [6][7][8][9] The techniques used in Brazil are in agreement with those of the Association of Official Analytical Chemists (AOAC) [10] and the National Health Surveillance Agency (Anvisa). Guidelines for bacterial agents, including Staphylococcus aureus, Pseudomonas aeruginosa and Salmonella choleraesuis, have been standardised, and adaptations for evaluation against fungi are required.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations